Antecedents of Perceived Job Commitment among Employees of Local Government in Ilesha Metropolis (Quest Journal of Management and Social Sciences, 2020)
Background: Employee commitment primarily focuses on strong bonds between the organization and its employees. It has massive positive effects on organizations. Investigating the combined influence of the assorted psychological factors like work-family conflict, job stress and self-concept on perceived job commitment among employees of Local Government authority is helpful.Objective: The study investigates the antecedents of perceived job commitment among employees of Local Government in Ilesha Metropolis.Methods: Antecedents of perceived job commitment in this study are work-family conflict, job stress, and self-concept. The study has adopted survey method within a descriptive research design. The objective of the study was to determine the influence of work-family conflict, job stress and self-concept on perceived job commitment. Primary data were used. Data were collected using a structured questionnaire that had five scales in likert scale including personal data. 238 respondents, randomly selected across the three local government areas in Ilesha Metropolis, were used for the study. Only 189 questionnaires were returned, out of which 124 were found to be useful for the study.Results: Three hypotheses were tested and they revealed that self-concept, work-family conflict and job stress jointly have a positive and significant impact on perceived job performance. Furthermore, work-family conflict (β = 0.173; t = 9.119; p